INTEGRASI SOFT SKILLS DALAM PEMBELAJARAN AKIDAH AKHLAK UNTUK MEMBENTUK KARAKTER SISWA DI MTS DARUL FALAH REMBUL - Muhamad Hamzah; Biltiser Bachtiar Manti (STKIP Pesisir Selatan, 2026)
This study aims to analyze the integration of soft skills in Akidah Akhlak learning and its role in shaping students' character at MTs Darul Falah Rembul. The research employed a qualitative approach with a case study design. The research subjects consisted of the principal, Akidah Akhlak teachers, and students. Data were collected through observation, interviews, and documentation, while data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that the integration of soft skills in Akidah Akhlak learning was implemented through planning, implementation, and evaluation processes that emphasized communication, cooperation, responsibility, discipline, and honesty. The integration was carried out through group discussions, collaborative assignments, presentations, teacher role modeling, and religious habituation activities within the school environment. This integration contributed positively to the development of students' character, particularly in fostering religious values, discipline, responsibility, honesty, and social awareness. The successful implementation of soft skills integration was supported by teachers' commitment, a religious school environment, and continuous character-building programs. However, several challenges were identified, including differences in students' characteristics, external environmental influences, and limited instructional time.